The CDC Foundation's COVID-19 emergency response pilot project: a case study in knowledge brokering for older adults and caregivers - Alaina Whitton; Hailey Bednar; Rachel F Singer; Roy Ahn; Jessica Fox; Lauren Isaacs; Alycia Bayne (Sax Institute, 2023)
Objective: The coronavirus disease 2019 (COVID-19) public health emergency has disproportionately affected older adults and their caregivers, requiring evidence-based and coordinated efforts to meet their health and social needs. This paper describes the role of the CDC Foundation as a knowledge broker working with public health partners to rapidly meet the unmet health, social, and other needs of older adults and caregivers during the COVID-19 pandemic. Type of program or service: Qualitative case study using the Role Model for Knowledge Brokering framework to describe a project that translated public health research into practice during the COVID-19 pandemic response. Methods: This case study documents the experiences of a US-based foundation serving as a knowledge broker, carrying out three roles: establishing research partnerships to study unmet health, social, and other needs of older adults and caregivers during COVID-19; coordinating with partners to identify evidence-based strategies; and rapidly implementing four emergency response pilot projects. Results: The emergency response pilot projects created included: an online resource library - SearchFindHelp.org - of public health programs and resources for organisations serving older adults and caregivers; digital literacy training for older adults and caregivers; multicultural caregiver tools to serve rural and Asian American and Pacific Islander older adults; and a grant program to expand local, direct services for older adults. SearchFindHelp.org had 46 781 new users and 101 908 total views from June 2021-March 2023. Older adults and caregivers who participated in digital literacy training from May-September 2021 were more likely to find health resources online and schedule and attend an online doctor's visit. A paid media campaign in December 2021 was launched to raise awareness of multicultural caregiver tools. Ten community organisations expanded direct, local services for older adults. Lessons learnt: This project highlights the valuable role a foundation can play as a knowledge broker in rapidly translating research into practice during a public health emergency response, to address emerging community needs.